Serum Testosterone Levels and Symptom-Based Depression Subtypes in Men - Rodgers, Stephanie; grosse Holtforth, Martin; Hengartner, Michael P.; Müller, Mario; Aleksandrowicz, Aleksandra A.; Rössler, Wulf; Ajdacic-Gross, Vladeta (Frontiers in Psychiatry, 2015)
The main objective of this preliminary study was to further clarify the association between T levels and depression by investigating symptom-based depression subtypes in a sample of 64 men. The data was taken from the ZInEP epidemiology survey. Gonadal hormones of a melancholic (n=25) and an atypical (n=14) depression subtype, derived from latent class analysis, were compared with those of healthy controls (n=18). Serum T was assayed using an ELISA procedure. Analysis of variance, analysis of covariance, non-parametrical tests and generalized linear regression models were performed to examine group differences. The atypical depressive subtype showed significantly lower T levels compared with the melancholic depressives. While accumulative evidence indicates that, beyond psychosocial characteristics, the melancholic and atypical depressive subtypes are also distinguishable by biological correlates, the current study expanded this knowledge to include gonadal hormones. Further longitudinal research is warranted to disclose causality by linking the multiple processes in pathogenesis of depression.